Spectral wave modelling of the extreme 2013/2014 winter storms in the North-East Atlantic. (15th November 2020) - Ruju, Andrea; Filipot, Jean-Francois; Bentamy, Abderrahim; Leckler, Fabien
Abstract: This works aims to investigate the impact of wind forcing datasets and wave breaking parameterizations on spectral wave model performance under extremely energetic conditions. For this purpose we used the wave model WaveWatch III to simulate the evolution of the highly energetic storms that occurred in winter 2013/2014 in the North-East Atlantic. We forced the wave model with two different wind datasets: one proceeding from the ECMWF ERA5 reanalysis dataset and the other from satellite observations. Moreover, two wave energy dissipation parameterizations were tested: Test471 and Test500. The model accuracy was assessed by comparing the output datasets with buoy data both in deep and coastal water. Moreover, wave height measurements from satellite were used to assess the model accuracy along storm tracks across the ocean. The accuracy of simulated results shows a significant dependence on the wind forcing and wave dissipation parameterization used. Error metrics computed under storm conditions at wave buoys are consistent with those computed along storm tracks. At the wave buoy locations, all datasets tend to underestimate wave parameters at the peaks of the storms. Highlights: The choice of the breaking parameterization and the wind forcing affects the performance of WaveWatch III under storms. The error metrics computed under storm conditions at wave buoys are consistent with those computed along storm tracks. A significant underestimation of extreme wave conditions at the storm peak is found. The high-resolution wind forcing ERA5 does not significantly improve the error statistics computed at the wave buoys.